Bioproduction dynamics ofPenaeus indicus H. Milne Edwards in modular system - Manikandavelu, D (Indian Journal of Fisheries, 2011)
Specific growth rate of white prawn Penaeus indicus was monitored in a miniaturemodular system. As the size of the module increased, reduction in ammoniageneration could be seen. Similar trend was also noticed with respect to organicload. Reduction in daily differential in oxygen as the module size increased, resultedin favourable specific growth rate in larger modules. The cumulative impact ofammonia, organic load (COD) and hydrogen sulphide was well indicated in specificgrowth rate. Surface area also appeared to play positive role on specific growthrate. Thus this modular system can serve as a new means to shrimp farming,striking a balance between ecological conservation and economic considerations